Median polish with covariate on before and after - I., Ajoge; Adam, Mohd. Bakri; Fitrianto, Anwar; Sadiq, A. Y. (International Organization of Scientific Research, 2016)
The method of median polish with covariate is use for verifying the relationship between before and after treatment data. The relationship is base on the yield of grain crops for both before and after data in a classification of contingency table. The main effects such as grand, column and row effects were estimated using median polish algorithm. Logarithm transformation of data before applying median polish is done to obtain reasonable results as well as finding the relationship between before and after treatment data. The data to be transformed must be positive. The results of median polish with covariate were evaluated based on the computation and findings showed that the median polish with covariate indicated a relationship between before and after treatment data.